2005
DOI: 10.1111/j.1467-954x.2005.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Older New Zealand Women Doing the Work of Christmas: A Recipe for Identity Formation

Abstract: Christmas, because it is rather a sentimental time you tend to look for the familiar and go back into what you remember in your childhood.' In the process of preparing family favourites or trying exciting new foods at Christmas, older New Zealand women construct self and family identities. This paper presents the New Zealand findings from an interpretive, multi-site research project exploring older women's experiences of food occupations at Christmas in Auckland, New Zealand, and Kentucky, USA and Songkran (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Within occupational science there has been some attention to the meaning of occupations embedded in a culture (Hannam 1997, Wright-St Clair et al 2005, Beagan and D'Sylva 2011). Hannam's (1997) study of five English women examined the meaning of tea drinking and identified six shared meanings for tea drinking: meaning through the reasons for drinking tea, meaning through the senses, meaning through the objects used, meaning through temporality, meaning through social context and meaning through changes in lifestyle.…”
Section: Meaningful Occupationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within occupational science there has been some attention to the meaning of occupations embedded in a culture (Hannam 1997, Wright-St Clair et al 2005, Beagan and D'Sylva 2011). Hannam's (1997) study of five English women examined the meaning of tea drinking and identified six shared meanings for tea drinking: meaning through the reasons for drinking tea, meaning through the senses, meaning through the objects used, meaning through temporality, meaning through social context and meaning through changes in lifestyle.…”
Section: Meaningful Occupationsmentioning
confidence: 99%
“…Hannam's (1997) study of five English women examined the meaning of tea drinking and identified six shared meanings for tea drinking: meaning through the reasons for drinking tea, meaning through the senses, meaning through the objects used, meaning through temporality, meaning through social context and meaning through changes in lifestyle. Wright-St Clair et al (2004Clair et al ( , 2005 explored the meaning of preparing food for cultural events, such as Christmas. These studies demonstrated rich shared meanings related to connection with family, culture and tradition, emphasising the significance of the sociocultural context in this study of Maltese band musicians.…”
Section: Meaningful Occupationsmentioning
confidence: 99%
“…Such a festival, and its associated myths and rituals which has wider implications for society beyond its temporal location, promulgate women at the heart of home. At this time and in this place, feminist theory shows that the organization of home-work reproduces relations of kinship, gender relations and subjugation (Adams, 1989;Caplow, 1982) whilst also being a site for women's identity and human values (Wright-St Clair et al, 2005) and, we add, moral choice.…”
Section: Discussionmentioning
confidence: 95%
“…The recent adoption of Valentine's Day by middle-class urban Ghanians allows them to demonstrate their allegiance to modern global ideas of love and marriage [12], and the celebration of Kwanzaa has been used by some middle-class Black Americans to promote their ethnic identity [25]. Moreover, the work women do to create family celebrations for holidays such as Thanksgiving and Christmas contributes to their self-perceived and socially constructed identities as cooks and caregivers [9,32]. Thus, holidays provide valuable opportunities to investigate societal values and normative conceptions of behavior and identity.…”
mentioning
confidence: 99%